2019
DOI: 10.1111/jdi.13062
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between physical activity and blood glucose is independent of sex, menopause status and first‐degree family history of diabetes

Abstract: Aims/IntroductionExercise training is a recognized strategy central to the prevention, treatment, and management of diabetes and prediabetes. The aim of the present study was to investigate the association between physical activity and blood glucose, as well as the influence of sex, menopause status and family history of diabetes.Materials and MethodsParticipants with normal weight were selected from Risk Evaluation of Cancers in Chinese Diabetic Individuals: A Longitudinal Study, and divided into inactive (mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A diabetes‐specific instrument, where patients look for patterns in their perceived stress levels and their blood glucose levels, may help patients to understand the relationship between stress and blood glucose levels 53 . A higher degree of physical activity can lower FPG, 54 and therefore, a change in exercise pattern could cause variability in FPG. Specific exercise recommendations are discussed in a later section.…”
Section: Monitoringmentioning
confidence: 99%
“…A diabetes‐specific instrument, where patients look for patterns in their perceived stress levels and their blood glucose levels, may help patients to understand the relationship between stress and blood glucose levels 53 . A higher degree of physical activity can lower FPG, 54 and therefore, a change in exercise pattern could cause variability in FPG. Specific exercise recommendations are discussed in a later section.…”
Section: Monitoringmentioning
confidence: 99%
“…Participants passed a screening for TMS contraindications [18] and were identified as right-handed using a modified handedness questionnaire [19]. Inactive individuals were excluded using the International Physical Activity Questionnaire (IPAQ, <600 MET-minutes/week) to reduce the risk of influence from prediabetic impairment of glucose metabolism, which is inversely correlated with physical activity level [20]. This study was approved by the Hamilton Integrated Research Ethics Board (HiREB) and conformed to the declaration of Helsinki.…”
Section: Participantsmentioning
confidence: 99%
“…Our study found physical activity to have an inverse association with the blood glucose level; this could be a reason behind the lower incidence of diabetes among the tribal participants. A recent study conducted among Chinese women reveals that a higher degree of physical activity was associated with lower blood glucose level regardless of sex, menopausal status and first-degree family history of diabetes [ 65 ]. Physical inactivity and obesity are critical and modifiable risk factors of diabetes; this could be a justification of the increased blood glucose level among the urban Hindu caste participants as most of them were found to be engaged in sedentary activities.…”
Section: Discussionmentioning
confidence: 99%